Recent Advances in Chitosan-based Nanocomposite Membrane Materials for Water Treatment - Zhang, Ziao; Lu, Yujie; Zhao, Yiman; Wu, Shuping (Journal of Chemical Engineering Research Updates, 2023)
In recent years, research on chitosan (CS)-based nanocomposite membranes has made significant progress in the field of water treatment. This innovative membrane material incorporates a variety of excellent biological properties, including the biocompatibility and adsorption properties of the natural polymer chitosan (CS) and the introduction of nanotechnology. Furthermore, it enables the composite material to have excellent functional characteristics, such as higher water flux and selectivity. Furthermore, the enhancement of the structural and intrinsic properties of membrane materials will facilitate the attainment of further advancements in a multitude of performance characteristics, including stability, durability, and adsorption selectivity. Consequently, this field has become a promising area of research in water treatment technology, attracting extensive research and attention. However, the publication of a large number of related research reports in recent years, accompanied by numerous and complex performance optimization schemes and research ideas, has resulted in a paucity of articles that summarize these performance optimization strategies and research paths. Consequently, there are few meaningful references for subsequent research. In light of the aforementioned considerations, this paper will provide a comprehensive review of the most recent research advances in the field of water treatment, with a particular focus on the latest research strategies and frameworks for optimizing the performance of related materials. Furthermore, this paper will illustrate the innovative and beneficial applications of such materials from various vantage points, including their sources and preparation processes. It is anticipated that this paper will serve as a valuable source of inspiration for further research in this field.